Nutrition in Pediatric Patients and Vulnerable Populations: Updates and Advances - Maria G. Grammatikopoulou; Tonia Vassilakou (MDPI AG, 2024)
Nutrition is a modifiable factor of paramount importance for the prevention and attainment of health and the development of youngsters [...]